Critical service-learning as revolutionary pedagogy : a project of student agency in action - Porfilio, Bradley J.; Hickman, Heather (Critical constructions., 2011)
This volume, offering a critical perspective on studies on education and society is a valuable resource to instructors who teach in the fields of teacher education, social studies, educational leadership, social work, social, cultural and philosophical foundations of education, sociology, political science, and global studies as well as their students.